Anteseden Kepuasan Pembeli Melakukan Transaksi M-Commerce: Eksplorasi Efek Moderasi dari Kustomisasi Tampilan M-Commerce - Cahyo, Karno Nur; Achmad Fatkharrofiqi; Haris Dermawan; Dwiza Riana (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
This study aims to determine the most significant factor statistically influencing customer satisfaction in the purchase transaction process using mobile commerce to test the moderating effect of customization or efforts to adapt m-commerce to consumer desires. Respondents who filled out the survey consisted of 125 respondents, spread over a span of 1 month, for customers who in the last 12 months have used m-commerce for buying and selling transactions. The results of this study are the customer trust factor, the perceived enjoyment factor when using m-commerce, the moderating effect of customization on usage benefits factor, and the customization factor are the 4 factors that most influence customer satisfaction. These findings are useful for M-commerce providers to focus their development on aspects of customer trust, customer enjoyment, and customization.